Sensors, Medical Images and Signal Processing: - Depeursinge, A.; Müller, H.; Section Editors for the IMIA Yearbook Section on Sensor, Signal and Imaging Informatics (Yearbook of Medical Informatics, 2011)
To summarize excellent research in the field of medical sensor, signal and imaging informatics published in the year 2010.Synopsis of the articles selected for the IMIA (International Medical Informatics Association) Yearbook 2011.Current research in the field of sensors, signal, and imaging informatics is characterized by theoretically sound techniques and evaluations with focus in imaging informatics. When compared to research on sensors and signals, imaging research represent the majority of published papers in 2010. Research published in 2010 was characterized by an increased participation of the clinicians in the study design, implementation and validation of computerized diagnosis aid tools.The best paper selection of articles on sensors, signal, and imaging informatics shows examples of excellent research on methods concerning theoretically sound original development in this field.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; image processing; signal processing; medical sensors